Light and shadow on innovative clinical trial designs: reflections from the EORTC-PAMM course on 'preclinical and early-phase clinical pharmacology'. Issue 11 (2nd November 2019) - Leonetti, Alessandro; Boyd, Lenka; Giuliani, Jacopo; Giovannetti, Elisa; Garajová, Ingrid
ABSTRACT: Introduction : In the era of 'precision' oncology, novel clinical trial designs have emerged, in order to better address the final goal of translating the above-mentioned preclinical discoveries into the clinic. Nonetheless, in aiming to achieve the greatest clinical benefit to patients, some limitations of these novel approaches from the statistical, methodological and practical point of view need to be overcome. Areas covered : In the present review, a short overview of basket trials, umbrella trials and platform trials are discussed, in particular advantages and disadvantages of such experimental approaches. Expert opinion : Master protocols represent the future of clinical oncology research. The possibility of investigating multiple biomarkers and therapeutic regimens under one study is a strong advantage over traditional trials, and it can lead to quick implementation of new, promising treatments or biomarkers into the clinic.